Three-dimensional velocity structure models in and around the Kathmandu Valley, Central Nepal - Kazuki Koketsu; Haruhiko Suzuki; Yujia Guo (Earth, Planets and Space, 2024)
Abstract We analyzed observations of microtremors and seismic ground motion to determine the depths of sedimentary interfaces and basement surface in the Kathmandu Valley. The results of these analyses and a reflection survey were combined to produce a data set of seismic depths for sedimentary interfaces and basement surface in the valley. Moreover, we introduced a data set of gravimetric depths, which had been produced for the basement surface from gravity observations. Because both sets of data differ in accuracy and number, we adopt the Sequential Gaussian Co-Simulation to generate the depth distributions of the sedimentary interfaces and basement surface. This method includes the cokriging approach, wherein the seismic and gravimetric depths are used as primary and secondary data, respectively. A three-dimensional velocity structure model of the Kathmandu Valley was constructed from the obtained depth distributions, which showed that the sedimentation in the valley is mainly related to the Paleo-Kathmandu Lake. Subsequently, we incorporated this model into a previous regional-scale model, and revised the latter to solve the issues of the extension of the underthrusting lithosphere and the S-wave velocity in its adjacent area. Graphical Abstract